Trauma-related disorders and the bodily self: current perspectives and future directions - Laricchiuta, Daniela; Garofalo, Carlo; Mazzeschi, Claudia (Frontiers in Psychology, 2023)
Trauma-related disorders are debilitating psychiatric conditions that influence people who have directly or indirectly witnessed adversities. Dramatic brain/body transformations and altered person's relationship with self, others, and the world occur when experiencing multiple types of traumas. In turn, these unfortunate modifications may contribute to predisposition to trauma-related vulnerability conditions, such as externalizing (aggression, delinquency, and conduct disorders) problems. This mini-review analyzes the relations between traumatic experiences (encoded as implicit and embodied procedural memories) and bodily self, sense of safety for the own body, and relationship with others, also in the presence of externalizing conducts. Furthermore, an emerging research area is also considered, highlighting principles and techniques of body-oriented and sensorimotor therapies designed to remodel bodily self-aspects in the presence of trauma, discussing their potential application with individuals showing externalizing problems.